Comparative Effectiveness of ’Acronym’ and ’Acrostic’ Mnemonics on Short Time Memorization of Anatomical Information among Bangladeshi Medical Undergraduates - Akhter, Najnin; Shamim, Khondker Manzare (Bangladesh Journal of Medical Education, 2025)
Background: Effectiveness of different mnemonics have been established by several researches. But in the extensive domain of Anatomy, the effectiveness of using different mnemonics or memory devices like 'Acronym' and 'Acrostic' for remembering huge amounts of information were neither put in visible format nor their individual effectiveness were analyzed. Objective: This research aimed to evaluate the comparative effectiveness of 'Acronym' and 'Acrostic' mnemonics on short time memorization of anatomical information among Bangladeshi medical undergraduates. Methods: This cross-sectional analytical research was carried out in the Department of Anatomy, Bangabadhu Sheikh Mujib Medical University (BSMMU) from March, 2017 to February, 2018. Ninety three (93) first year Bangladeshi medical undergraduates of two public medical colleges of Dhaka city, Bangladesh, were selected by convenient sampling and then they were divided into three groups: 'Acronym', 'Acrostic' & 'Control' groups. A demonstration on how to use mnemonics in learning for remembering large number of anatomical information was given by a PowerPoint Presentation including total procedures of data collection. Data were collected and analyzed by ANOVA post hoc to compare effectiveness of two mnemonics over control group. Results: Performance of both 'Acronym' and 'Acrostic' groups were found statistically more significant (p value less than 0.05) than ‘Control’ group. While comparing the performance of 'Acronym' and 'Acrostic' groups, 'Acrostic' was statistically more significant than 'Acronym'. Conclusion: Application of mnemonics for short time memorization of anatomical information reflects better impact on retention. With proper training to teaching faculties, it could be used in future teaching-learning of recalled topics. BJME, Volume-16, Issue-02, July 2025: 3-9